Pengaruh Keputusan Manajemen Keuangan Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening - Irma Christiana; Linzzy Pratami Putri (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this research is to examine the effect of financial management decisions on firm value with profitability as an intervening variable in insurance companies listed on the Indonesia Stock Exchange. In order to answer the hypothesis, this study uses an associated quantitative method. The sampling technique was the purposive sampling method so that 8 companies were selected that met the criteria from a population of 14 companies, the data used were secondary data and time series. Data analysis using regression and path analysis. The findings of this study are the debt to equity ratio has a positive and significant effect on return on equity, but the price earnings ratio and the dividend payout ratio have a negative and insignificant effect on return on equity. The next finding is that the price earning ratio and return on equity have a positive and significant effect on price to book value, while the debt to equity ratio and dividend payout ratio have a negative and insignificant effect on price to book value. Furthermore, profitability is able to mediate the relationship between financial management decisions and firm value.